Rotational Rest Frequencies and First Astronomical Search of Protonated Methylamine - Schmid, Philipp C.; Thorwirth, Sven; Endres, Christian P.; Töpfer, Matthias; Sánchez-Monge, Álvaro; Schwörer, Andreas; Schilke, Peter; Schlemmer, Stephan; Asvany, Oskar (Frontiers in Astronomy and Space Sciences, 2022)
We report first laboratory rest frequencies for rotational transitions of protonated methylamine, CH3NH3+, measured in a cryogenic 22-pole ion trap machine and employing an action spectroscopy scheme. For this prolate symmetric top molecule thirteen transitions between 80 and 240 GHz were detected in the ground vibrational state, covering JK= 2K−1K up to JK= 6K−5K with K= 0,1,2. Some transitions exhibit noticeable structure that is attributed to internal rotation splitting. As the CN radical and several of its hydrogenated and protonated forms up to methylamine, CH3NH2, are well known entities in the laboratory and in space, protonated methylamine, CH3NH3+, is a promising candidate for future radio astronomical detection